(3TQM GdcGajI GdTGajI aj GdfMhs - (3CHhYHO Gddg HOQGdOjf eMeO Hf eMeO Hf YHO Gddg Hf eGdc GdWGFjs; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GHf eGdc SCdfj Cf CJdh GdcGajI GdTGajI HTQM JNa Hg GdeDhfI aCLHJ OYhJg s
(3BNQgG (B:s
(3heKdg CjVkG GdeNOY hgh HjJ UZjQ aj UOQ GdHjJ GdcHjQ, hQhi CjVkG GdJKdjK aj eje eUMa ced GdcJGH s
(3gh cJGH efXhes
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs